MTOR Inhibition Role in Cellular Mechanisms. (February 2018) - Zaza, Gianluigi; Granata, Simona; Caletti, Chiara; Signorini, Lorenzo; Stallone, Giovanni; Lupo, Antonio
Abstract : Abstract: The mammalian target of rapamycin inhibitors (mTOR-I), drugs widely used in transplant medicine and oncology, exert their function by inhibiting a serine/threonine kinase with a pivotal role in cellular metabolism and in a wide range of eukaryotic biological/cellular functions and signaling networks. Additionally, as largely described, the inhibition of mTOR has a major impact on cellular metabolism by stimulating synthesis of proteins and lipids, inhibiting catabolic processes, such as lysosome biogenesis and autophagy, and controlling cell survival, cytoskeleton organization, lipogenesis, and gluconeogenesis. All these biological functions are essential to guarantee body homeostasis and survival. Therefore, it is necessary for clinicians and researchers to better understand this complex pathway to ameliorate patients' treatment empathizing therapeutic effects to minimize/avoid toxicities and to propose new valuable research strategies. The aim of this article has been to underline the complexity of the mTOR pathway and to review the recent literature describing the consequences of its inhibition on several cellular functions including (a) protein synthesis, (b) cell cycle, (c) lipid metabolism, (d) energy metabolism, (e) autophagy, (f) angiogenesis, (g) glucose metabolism, (h) cytoskeleton remodeling, (i) epithelial to mesenchymal transition, and (j) immune cells development and function.